Sustainable Business as a Strategy for Peacebuilding - Rosas-Patiño, Gelber; Jiménez-Zapata, Elvia María; Sánchez-Castillo, Verenice (Journal of Ecohumanism, 2024)
This study analyzes the underexplored nexus between sustainable business and peacebuilding, revealing critical gaps and opportunities through bibliometric analysis (2018–2023). While sustainable business research dominates in volume (4,115 publications in 2023 vs. 298 for peacebuilding) and influence (15.6 vs. 5.1 citations/article), its focus on environmental and economic metrics often overlooks conflict dynamics. Conversely, peacebuilding studies prioritize post-conflict governance but neglect integration with inclusive economic models, with only 2% of sustainable business literature addressing “conflict.” Colombia exemplifies this divide: a global leader in peacebuilding research (9.7% of global output) but a marginal contributor to sustainable business (0.7%), despite its potential to pioneer hybrid models like conflict-sensitive agroindustry. The authors identified seven transdisciplinary research priorities to advance the joint field. These address systemic gaps, including the marginalization of Africa/Middle East in both fields and the disconnect between global sustainability frameworks and grassroots realities. The findings advocate for South-South collaboration, context-sensitive adaptations of ESG standards, and structural reforms. While technology and education are enablers, sustainable peace requires centering marginalized communities in business models and policy design. For Colombia, aligning renewable energy projects with ancestral knowledge and victim reintegration programs emerges as a critical pathway.